Sulfide-based solid electrolyte and method for manufacturing the same
Patent Information
- Application Number
- KR1020237012122
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-13
- Filing Date
- 2021-10-13
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2041-10-13
Smart Images

Figure 112023039853041-PCT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a sulfide-based solid electrolyte used in lithium-ion secondary batteries and a method for manufacturing the same. Background Technology
[0002] Lithium-ion secondary batteries are widely used in portable electronic devices such as mobile phones and notebook personal computers.
[0003] Conventionally, liquid electrolytes have been used in lithium-ion secondary batteries, but there were concerns about leakage or ignition, so it was necessary to enlarge the case for safety design. In addition, improvements were desired regarding the short battery life and narrow operating temperature range.
[0004] In this regard, all-solid-state lithium-ion secondary batteries that use a solid electrolyte as the electrolyte are attracting attention, as they offer the potential for improved safety, high-speed charging and discharging, and miniaturization of the case.
[0005] Solid electrolytes are broadly classified into sulfide-based solid electrolytes and oxide-based solid electrolytes. Sulfide ions constituting sulfide-based solid electrolytes have a higher polarization rate and exhibit higher ionic conductivity compared to oxide ions constituting oxide-based solid electrolytes. As a sulfide-based solid electrolyte, Li 10 GeP2S 12 LGPS-type crystals such as Li6PS5Cl, agirodite-type crystals such as Li7P3S 11 LPS crystallized glass, such as crystallized glass, is known.
[0006] Patent Document 1 can be cited as an example in which an agirodite-type sulfide-based solid electrolyte is disclosed. The sulfide-based solid electrolyte disclosed in Patent Document 1 has a cubic crystal structure belonging to space group F-43m, and composition formula: Li 7-x PS 6-X Ha X(Ha contains a compound represented as Cl or Br)(x=0.2–1.8), and also L * a * b * The L value of the colorimetric system is 60.0 or higher. This is intended to increase charge / discharge efficiency and cycle characteristics by increasing lithium ion conductivity and lowering electron conductivity. Prior art literature
[0007] International Publication No. 2015 / 012042 The problem to be solved
[0008] Sulfide-based solid electrolytes using agirodite-type crystals can achieve high lithium-ion conductivity due to the inclusion of halogen elements. On the other hand, halides are highly corrosive, and if the amount of halogen elements contained in the sulfide-based solid electrolyte is excessive, there is a concern regarding corrosion of the metals constituting the lithium-ion secondary battery.
[0009] Accordingly, the present invention aims to provide a sulfide-based solid electrolyte for use in lithium-ion secondary batteries and a method for manufacturing the same, which exhibits high lithium-ion conductivity even when the elemental ratio of halogen elements in an agirodite-type crystal is kept below a certain level. means of solving the problem
[0010] The inventors, after repeated careful examination, discovered that the above problem could be solved by using a sulfide-based solid electrolyte having an agirodite-type crystal structure having a specific peak in the X-ray diffraction spectrum, and thus completed the present invention.
[0011] That is, the present invention relates to the following [1] to [7].
[0012] [1] A sulfide-based solid electrolyte used in a lithium-ion secondary battery, and in the X-ray diffraction spectrum using Cu-Kα rays, it has peaks A and B with full width at half maximum of 0.07° each within the range of 2θ = 30.3±0.5°, and the difference in diffraction angle (2θ) between peak A and peak B is 0.05° or more, and Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2이고, Ha은 할로겐 원소이다.)로 표시되는 아기로다이트형의 결정 구조를 갖는 황화물계 고체 전해질.
[0013] [2] A sulfide-based solid electrolyte described in [1] having a peak C between peak A and peak B.
[0014] [3] A sulfide-based solid electrolyte described in [1] or [2], wherein the peaks A and B are peaks originating from two types of agirodite-type crystal structures with lattice constants that differ by more than 0.02 Å.
[0015] [4] A sulfide-based solid electrolyte described in any one of [1] to [3], wherein, in the X-ray diffraction spectrum using Cu-Kα rays after heat treatment for 1 hour at a temperature above 400°C and below the thermal decomposition temperature, at least one of the following phenomena is observed: a decrease in the peak intensity ratio of peak A, an increase in the peak intensity ratio of peak B, and the appearance of peak C or an increase in the peak intensity ratio of peak C, wherein peak C is located on the higher angle side than peak A and on the lower angle side than peak B.
[0016] [5] A sulfide-based solid electrolyte used in lithium-ion secondary batteries, having peaks D and E, each with a full width at half maximum of 0.07° in the range of 2θ=30.3±0.5° in the X-ray diffraction spectrum using Cu-Kα rays, and the difference in diffraction angle (2θ) between peak D and peak E is 0.02 to 0.4°, and Li a PSb Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2이고, Ha은 할로겐 원소이다.)로 표시되는 아기로다이트형의 결정 구조를 갖고, 400℃ 이상 열분해 온도 이하의 온도에서 1시간의 열처리를 행해도, 상기 X선 회절 스펙트럼이 변화되지 않는, 황화물계 고체 전해질.
[0017] [6] A method for manufacturing a sulfide-based solid electrolyte used in lithium-ion secondary batteries, comprising mixing raw materials containing Li, P, S and Ha and heating and melting them, followed by crystallizing them by rapid cooling under atmospheric pressure, wherein Ha is a halogen element and Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2이고, Ha은 할로겐 원소이다.)로 표시되는 다른 2종 이상의 아기로다이트형의 결정 구조를 갖는, 황화물계 고체 전해질의 제조 방법.
[0018] [7] A method for manufacturing a sulfide-based solid electrolyte described in [6], wherein, after the crystallization, heat treatment is performed at 200 to 600°C for 0.1 to 10 hours. Effects of the invention
[0019] According to the sulfide-based solid electrolyte of the present invention, high lithium-ion conductivity can be achieved even if the elemental ratio of halogen elements in the agirodite-type crystal is below a certain level. Therefore, it is very useful as a solid electrolyte for lithium-ion secondary batteries, and thereby, an improvement in the battery characteristics of lithium-ion secondary batteries can be expected. Brief explanation of the drawing
[0020] Figure 1 is a part of the XRD spectrum of the solid electrolyte of Example 1. Figure 2 is a part of the XRD spectrum of the solid electrolyte of Example 2. Specific details for implementing the invention
[0021] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and may be implemented with arbitrary modifications within the scope that does not deviate from the gist of the present invention. Furthermore, the notation "~" indicating a numerical range is used to mean that the values described before and after it are included as lower and upper limits.
[0022] Sulfide-based solid electrolytes
[0023] The sulfide-based solid electrolyte according to the present embodiment (hereinafter simply referred to as "solid electrolyte") is used in a lithium-ion secondary battery and has an agirodite-type crystal structure. The agirodite-type crystal structure is Li a PS b Ha c When expressed as such, the ratio of each element is 5≤a≤7, 4≤b≤6, and also 0 <c≤2의 관계를 충족시킨다. 또한, Ha은 할로겐 원소를 나타낸다.
[0024] The solid electrolyte according to the present embodiment has peaks A and B within the range of 2θ = 30.3 ± 0.5° in the X-ray diffraction (XRD) spectrum using Cu-Kα rays. For convenience, the peak on the lower angle side is defined as peak A, and the peak on the higher angle side is defined as peak B. The difference in diffraction angles (2θ) between peak A and peak B is 0.05° or more. In addition, the full width at half maximum of peaks A and B is 0.07° or more, respectively.
[0025] Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2)로 표시되는 아기로다이트형의 결정 구조는, Li, P, S 및 Ha을 포함한다. Ha은 할로겐 원소이고, F, Cl, Br 및 I으로 이루어지는 군에서 선택되는 적어도 1종의 할로겐 원소이다.
[0026] In the XRD spectrum using Cu-Kα rays, the solid electrolyte according to the present embodiment has peaks A and B sequentially from the lower angle side within the range of 2θ = 30.3 ± 0.5°. The difference in the diffraction angle (2θ) of these peaks is 0.05° or more. This means that the solid electrolyte has two or more types of agarodite-type crystal structures with different compositions.
[0027] A solid electrolyte having two or more types of agirodite-type crystal structures is different from a mixture of two or more powders having different compositions of agirodite-type crystal structures. This can be distinguished by the full width at half maximum of peaks A and B.
[0028] Specifically, the solid electrolyte according to the present embodiment has a full width at half maximum of 0.07° or greater for peaks A and B in the XRD spectrum. On the other hand, in a mixture of two or more powders having different compositions of agirodite-type crystal structures, the full width at half maximum of the peaks in the XRD spectrum is less than 0.07°. That is, the solid electrolyte according to the present embodiment is not a mixture in which the crystals coexist on the order of mm or μm, but a solid electrolyte in which two or more types of agirodite-type crystals coexist on the order of hundreds of nanometers or tens of nanometers. Furthermore, the full width at half maximum of the peaks will be described later.
[0029] By the coexistence of two or more types of agirodite-type crystals on the order of hundreds of nanometers or tens of nanometers, Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2)의 식 중 c로 표시되는 할로겐 원소의 원소비가 2 이하의 낮은 값이라도, 높은 리튬 이온 전도율을 실현할 수 있다.
[0030] Although the reason is not clear, the solid electrolyte according to the present embodiment is realized when, during the manufacturing of the solid electrolyte, a melting process is performed and then cooled to obtain an agrodite-type crystal. It is presumed that the seed crystal initially precipitated during the cooling process from the molten state is a high-temperature stable phase. Therefore, the agrodite-type crystal that grows using that seed crystal as a nucleus has different sites for lithium ions, sulfur anions, and halogen anions compared to crystals produced by a normal solid-state reaction, and it is thought that this affects the lithium ion conductivity. Generally, the high-temperature stable phase tends to have high lithium ion conductivity, but in the agrodite-type crystal of the present embodiment, agrodite-type crystals of multiple compositions containing the high-temperature stable phase are precipitated during the cooling process from the molten state. Therefore, it is believed that high lithium ion conductivity can be realized.
[0031] It can be confirmed that two or more types of agirodite crystals coexist on the order of hundreds of nanometers or tens of nanometers, rather than on the order of mm or μm, in addition to the full width at half maximum of the peaks, from the XRD spectra before and after heat treatment of the obtained solid electrolyte.
[0032] Specifically, if, after performing heat treatment for 1 hour at a temperature of 400°C or higher and below the thermal decomposition temperature of the solid electrolyte, at least one of the following phenomena is observed: a decrease in the peak intensity ratio of Peak A, an increase in the peak intensity ratio of Peak B, the manifestation of Peak C, or an increase in the peak intensity ratio of Peak C, then it can be said that two or more types of agirodite-type crystals coexist on the order of hundreds of nanometers or tens of nanometers. Here, Peak C is a peak that is higher angle than Peak A and lower angle than Peak B.
[0033] The phenomenon of a decrease in the peak intensity ratio of Peak A includes the phenomenon of Peak A disappearing. Furthermore, regarding Peak C, the phenomenon of an increase in the peak intensity ratio due to heat treatment presupposes that Peak C is observed prior to the heat treatment. The phenomenon of Peak C newly emerging due to heat treatment presupposes that Peak C is not observed prior to the heat treatment.
[0034] On the other hand, in the case of powders having an agirodite-type crystal structure with different compositions, that is, mixtures on the order of mm or μm, even if the same heat treatment is performed, the above-mentioned changes are not observed in the XRD pattern.
[0035] For example, FIG. 1 shows the spectrum near 2θ=30.3° of the XRD spectrum of Example 1 described below, and FIG. 2 shows the spectrum near 2θ=30.3° of the XRD spectrum of Example 2 described below. Example 2 is a solid electrolyte obtained by heat-treating the solid electrolyte obtained in Example 1 at 500°C for 1 hour. In addition, the XRD spectra shown in FIG. 1 and FIG. 2 show the result of eliminating the diffraction pattern caused by the Cu-Kα2 line among the Cu-Kα lines that serve as the source. Details regarding the elimination of the diffraction pattern caused by the Cu-Kα2 line will be described later along with the method of peak separation.
[0036] In the XRD spectrum before heat treatment shown in Fig. 1, from the raw data represented by the solid line, i.e., the untreated spectrum, peaks corresponding to peak A at 2θ=29.99° and peak B at 2θ=30.24° are clearly observed. However, when the peaks are separated through actual analysis, in addition to peak A represented by the dashed line and peak B represented by the dotted line, there is a peak at 30.11° near 2θ={(peak A+peak B) / 2} represented by the dotted line. This corresponds to peak C. Thus, by analysis, it is possible to separate the peaks into three peaks: peak A, peak B, and peak C. The method of peak separation will be described later.
[0037] In addition, in Example 1, a peak is also seen at 2θ = 30.66°. Although it is difficult to determine the detailed attribution of this peak, it is thought to be a peak of a cubic agirodite-type crystal with reduced symmetry or a cubic agirodite-type crystal with a lowered lattice constant due to the absence of lithium, etc. The solid electrolyte according to the present embodiment may have such a peak in addition to peaks A, B, and C.
[0038] In contrast, in the XRD spectrum after heat treatment at 500°C for 1 hour in Fig. 2, a sharp peak is visible around 2θ=30.11° from the original data shown as a solid line. However, when peak separation is performed, it can be seen that in addition to peak C shown as a dotted line, a peak is observed at 2θ=30.20° corresponding to peak B shown as a dashed line. Furthermore, the peak corresponding to peak A shown as a dashed line in Fig. 1 has disappeared, or the peak intensity ratio has decreased to the point where the peak cannot be detected.
[0039] As shown in Examples 1 and 2 in FIGS. 1 and 2, the solid electrolyte according to the present embodiment undergoes heat treatment, which causes a phenomenon in which the peak intensity ratio of peak C, which exists between peak A and peak B, increases. In addition, if peak C does not exist before heat treatment, a phenomenon in which peak C newly appears may occur through heat treatment.
[0040] In addition, by performing heat treatment simultaneously with or instead of the above phenomenon, phenomena such as a decrease in the peak intensity ratio of Peak A or an increase in the peak intensity ratio of Peak B may occur.
[0041] That is, it is desirable for the improvement of lithium-ion conductivity that, through heat treatment, at least one of the phenomena of a decrease in the peak intensity ratio of Peak A, an increase in the peak intensity ratio of Peak B, and the manifestation of Peak C or an increase in the peak intensity ratio of Peak C is observed. Furthermore, it is more desirable to observe an increase in the peak intensity ratio of at least one of Peak B and Peak C, and even more desirable to observe an increase in the peak intensity ratio of at least one of Peak B and Peak C along with a decrease in the peak intensity ratio of Peak A. Additionally, it is desirable to observe a decrease in the peak intensity ratio of Peak C and an increase in the peak intensity ratio of Peak B.
[0042] On the other hand, in the case of a mixture of powders having an agirodite-type crystal structure with different compositions, even after heat treatment, no such changes as described above are observed in the XRD pattern, and the difference in diffraction angle or the relative peak intensity ratio is maintained.
[0043] Figures 1 and 2 will be explained in more detail. The composition of the agirodite-type crystal structure, represented by the peak at 2θ = 29.99° corresponding to peak A prior to heat treatment, is Li a1 PS b1 Ha c1 , the composition of the agirodite-type crystal structure indicated by the peak at 2θ=30.24° corresponding to peak B is Li a2 PS b2 Ha c2 , the composition of the agirodite-type crystal structure indicated by the peak at 2θ=30.11° corresponding to peak C is Li a3 PS b3 Ha c3 It is assumed that...
[0044] From the relationship of the peak intensity ratios above, the content ratio of each composition in the solid electrolyte before heat treatment, which is Example 1, is Li a2 PS b2 Ha c2 >Li a1 PS b1 Hac1 >Li a3 PS b3 Ha c3 The relationship becomes. In contrast, in Example 2 after heat treatment, the above content ratio is Li a3 PS b3 Ha c3 >Li a2 PS b2 Ha c2 >>Li a1 PS b1 Ha c1 It becomes a relationship.
[0045] That is, in Example 2, by performing heat treatment, the existence ratio of the three types of agirodite-type crystal structures in Example 1 prior to heat treatment changes, and Li a1 PS b1 Ha c1 and Li a2 PS b2 Ha c2 The composition between, Li a3 PS b3 Ha c3 It became a solid electrolyte with an increased amount of agirodite-type crystal structure.
[0046] Thus, the manifestation of peak C or an increase in the peak intensity ratio due to heat treatment implies that the composition of at least one of peaks A and B has changed to the composition of peak C. Among these, it is desirable for the composition of peak A to change to the composition of peak C in terms of improving lithium-ion conductivity. Furthermore, from the perspective of improving lithium-ion conductivity, it is also desirable for the composition of at least one of peaks A and C to change to the composition of peak B due to heat treatment.
[0047] Peaks A and B, where the difference in diffraction angle (2θ) is 0.05° or greater, indicate that the crystal structure has two types of agirodite-type crystals with different compositions. Focusing on the peak position at 2θ = 30.3 ± 0.5° where peaks A and B are observed, regarding the agirodite-type crystal, particularly the cubic agirodite-type crystal, it is desirable for the lattice constants of the two types of crystals with a difference in diffraction angle (2θ) of 0.05° or greater to differ by 0.02 Å or more in terms of improving lithium-ion conductivity, and it is more desirable for the difference in lattice constants to be 0.03 Å or greater, and even more desirable for 0.05 Å or greater. Furthermore, in terms of crystal stability, it is desirable for the difference in lattice constants to be 0.2 Å or less, more desirable for 0.15 Å or less, and even more desirable for 0.1 Å or less.
[0048] The agirodite-type crystals indicated by peak B on the elevation side are composed of Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2)에 있어서 Ha의 원소비를 나타내는 c가, 높은 리튬 이온 전도율의 점에서, 0.3 이상이 바람직하고, 1 이상이 보다 바람직하고, 1.5 이상이 더욱 바람직하다. 또한, 금속 집전체 부식 억제의 점에서, c는 2 이하이고, 1.85 이하가 바람직하고, 1.7 이하가 보다 바람직하다.
[0049] The agirodite-type crystal represented by peak A on the lower angle side is composed of Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2)에 있어서 Ha의 원소비를 나타내는 c가, 높은 리튬 이온 전도율의 점에서, 0 초과이고, 0.5 이상이 바람직하고, 1 이상이 보다 바람직하다. 또한, 금속 집전체 부식 억제의 점에서는, c는 1.7 이하가 바람직하고, 1.6 이하가 보다 바람직하고, 1.5 이하가 더욱 바람직하다.
[0050] Li, the arirhodite-type crystal indicated by peak Aa1 PS b1 Ha c1 and, the agirodite-type crystal Li indicated by peak B a2 PS b2 Ha c2 The ratio of (Li a1 PS b1 Ha c1 :Li a2 PS b2 Ha c2 In terms of high lithium ion conductivity, 1:99 to 95:5 is preferred, 1:99 to 50:50 is more preferred, and 2:98 to 10:90 is even more preferred.
[0051] The difference in diffraction angles (2θ) between peak A and peak B should be 0.05° or more, but for the sake of improving lithium ion conductivity, it is preferable to have a difference of 0.06° or more, and more preferable to have a difference of 0.07° or more. In addition, for the sake of crystal stability, the difference in diffraction angles (2θ) should be 0.8° or less, more preferable to have a difference of 0.6° or less, and even more preferable to have a difference of 0.4° or less. Furthermore, in the analysis of the peaks, there may be cases where the difference in diffraction angles (2θ) between peak A and peak B is less than 0.05°, but in such cases, these peaks are combined and considered as a single peak.
[0052] The solid electrolyte according to the present embodiment preferably has a peak C between peaks A and B for improved lithium ion conductivity. The agirodite-type crystals represented by peak C are composed of Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2)에 있어서 Ha의 원소비를 나타내는 c가, 높은 리튬 이온 전도율의 점에서, 0.5 이상이 바람직하고, 1 이상이 보다 바람직하고, 1.5 이상이 더욱 바람직하다. 또한, 금속 집전체 부식 억제의 점에서, c는 1.9 이하가 바람직하고, 1.8 이하가 보다 바람직하고, 1.7 이하가 더욱 바람직하다.
[0053] In terms of improving lithium ion conductivity, Li a2 PS b2 Ha c2 and Li a3 PS b3 Ha c3 It is desirable for the proportion of to be large, and Li a1 PS b1 Ha c1 :(Li a2 PS b2 Ha c2 +Li a3 PS b3 Ha c3 The ratio indicated by ) is preferably 1:99 to 95:5, more preferably 1:99 to 50:50, and even more preferably 2:98 to 10:90.
[0054] The XRD spectrum of the solid electrolyte according to the present embodiment may have peaks at positions other than 2θ=30.3±0.5°. Peaks observed at other positions may also be separated into two or more peaks by performing peak separation, just like peaks within the range of 2θ=30.3±0.5°.
[0055] The preferred crystal structure of the agirodite-type crystal is cubic, for example, F-43m, but rhombohedral, tetragonal, or rectangular crystals with poor symmetry, or monoclinic crystals with poor symmetry, may also exist.
[0056] When the crystal structure of the agirodite type is cubic and the lattice constant is a=b=c, it is thought that structural changes due to heat treatment occur isotropically. Therefore, for other peaks observed in the range other than 2θ=30.3±0.5°, it is conceivable that phenomena such as an increase or decrease in the intensity ratio of peaks representing each crystal structure, or the appearance of new peaks, may be observed by performing heat treatment for 1 hour at a temperature above 400°C and below the thermal decomposition temperature.
[0057] In addition, even if the crystal structure of the agirodite type is not cubic, some structural change according to the crystal structure may occur through the above heat treatment.
[0058] In addition, a solid electrolyte after heat treatment as described below is also included in one embodiment of the present invention.
[0059] These embodiments are Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2이다.)로 표시되는 아기로다이트형의 결정 구조를 갖고, 리튬 이온 이차 전지에 사용되는 황화물계 고체 전해질이다. 이 고체 전해질은, Cu-Kα선을 사용한 X선 회절 스펙트럼에 있어서, 2θ=30.3±0.5°의 범위 내에, 피크 D 및 피크 E를 갖는다. 이러한 피크의 반값 전폭은 모두 0.07° 이상이고, 이러한 2개의 피크의 회절각(2θ)의 차는 0.02∼0.4°이다. 또한, 400℃ 이상 열분해 온도 이하의 온도에서 1시간의 열처리를 행해도, X선 회절 스펙트럼에 변화는 보이지 않는다.
[0060] Peaks D and E, with a difference in diffraction angle (2θ) of 0.02 to 0.4°, correspond to peak A or peak B and peak C, respectively, before heat treatment, and are two different types of agirodite crystals.
[0061] In the case where peak D is the low-angle side and peak E is the high-angle side, peaks D and E correspond to peaks A and C before heat treatment, respectively, or to peaks C and B before treatment, respectively.
[0062] When peaks D and E correspond to peaks A and C, respectively, there may be an additional peak F on the high-angle side corresponding to peak B. Additionally, when peaks D and E correspond to peaks C and B, respectively, there may be an additional peak G corresponding to peak A on the low-angle side. In this case, the full width at half for peaks F and G is preferably 0.07° or more. Furthermore, the difference in diffraction angle (2θ) between peak F and peak E is preferably 0.05 to 0.4°, and the difference in diffraction angle (2θ) between peak G and peak D is preferably 0.05 to 0.4°.
[0063] The difference in diffraction angles (2θ) between peak D and peak E can be 0.02 to 0.4°, but for the sake of improving lithium ion conductivity, it is preferable for it to be 0.05° or more, more preferable for it to be 0.07° or more, and even more preferable for it to be 0.09° or more. In addition, for the sake of crystal stability, the difference in diffraction angles (2θ) is preferable for it to be 0.3° or less, and more preferable for it to be 0.2° or less. Also, the preferred range for the difference in diffraction angles (2θ) between peak F and peak E, or the difference in diffraction angles (2θ) between peak G and peak D, is the same as above.
[0064] The solid electrolyte according to the present embodiment, comprising the crystal structures of the agirodite type represented by peaks D and E, can adjust the ratio of crystals or the difference in diffraction angles, etc., by the conditions of heat treatment.
[0065] In addition, whether the solid electrolyte has undergone heat treatment can be determined not only by the absence of a change in the XRD spectrum when additional heat treatment is performed, but also by the degree of change in lithium-ion conductivity. A change in the XRD spectrum means that the values of the diffraction angles (2θ) of peaks D and E do not change, or even if they do change, the difference in diffraction angles before and after heat treatment is 0.05° or less. In addition, it is preferable that the change in the peak intensity ratio before and after heat treatment is 0.1 or less. It is preferable that the degree of change in lithium-ion conductivity before and after heat treatment is 0.5 mS / cm or less.
[0066] This additional heat treatment is performed for 1 hour in a temperature range of 400°C or higher and pyrolysis temperature or lower.
[0067] Li indicating the composition of agirodite-type crystals a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2)에 있어서, Ha으로 표시되는 할로겐 원소는, F, Cl, Br 및 I으로 이루어지는 군에서 선택되는 적어도 1종이다. 결정이 아기로다이트형이 되기 쉬운 점에서, Cl 및 Br 중 적어도 한쪽을 포함하는 것이 바람직하고, Cl을 포함하는 것이 보다 바람직하고, Cl 단체 또는 Cl 및 Br의 혼합체가 더욱 바람직하다.
[0068] The crystallite size of the agirodite-type crystal is preferably small from the perspective of obtaining good lithium ion conductivity when manufacturing a lithium ion battery by finely grinding a solid electrolyte, and specifically, it is preferably 1000 nm or less, more preferably 500 nm or less, and even more preferably 250 nm or less. The lower limit of the crystallite size is not particularly limited, but is typically 5 nm or more.
[0069] Although the crystallite size after heat treatment increases compared to before heat treatment, it is desirable that the crystallite size remains within the above range even after heat treatment.
[0070] The crystallite size can be calculated from the full half width of the peaks in the XRD pattern.
[0071] The secondary particle size of the agirodite-type crystal is preferably small from the perspective of obtaining good lithium ion conductivity when manufacturing a lithium ion battery by finely grinding the solid electrolyte, and specifically, it is preferably 10 μm or less, more preferably 3 μm or less, and even more preferably 1 μm or less. The lower limit of the secondary particle size is not particularly limited, but is typically 0.1 μm or more.
[0072] The secondary particle size can be measured using a microtrack device.
[0073] The full width at half maximum of each peak is 0.07° or greater, preferably 0.075° or greater, more preferably 0.08° or greater, and even more preferably 0.09° or greater, as it is preferable for the crystallite size to be small. In addition, there is no specific upper limit for the full width at half maximum, but it is usually obtained within 0.5°, and if the full width at half maximum is greater than that, it is better to increase the number of peaks and re-analyze. The analysis method for determining the full width at half maximum will be described later.
[0074] In the present embodiment, the agirodite-type crystal structure may include oxide anions. For example, it is preferable to include oxide anions of a Q0 structure in which a metal atom (M) and an oxygen atom (O) are bonded, from the perspective that the heat resistance of the crystal is improved and it can exist stably without decomposing even when heat treatment is performed at high temperatures.
[0075] Here, the Q0 structure refers to a structure in which all oxygen atoms bonded to the central cation M are non-bridged oxygen atoms. For example, when M is Si, the oxide that becomes SiO2 is a silicate ion, i.e., SiO4 4- It means existing as an oxide anion called...
[0076] The elements constituting the oxide anion may include M and O, and M is at least one element selected from the group consisting of metal elements and metalloid elements of groups 2 to 14 of the periodic table. In addition, the oxide anion may be of only one type or may include multiple types.
[0077] Metallic elements of groups 2 to 14 are elements of groups 2 to 12 of the periodic table, elements of group 13 other than B, and elements of group 14 other than C, Si, and Ge.
[0078] The metalloid elements of groups 2 to 14 are B, Si, and Ge among the elements of groups 13 and 14 of the periodic table.
[0079] In addition, the presence of MO bonds or Q0 structures in oxide anions can be confirmed by Raman spectroscopy or nuclear magnetic resonance (NMR) measurements. Furthermore, the presence of oxide anions with Q0 structures in the crystal structure, that is, in the anion sites of the crystal, can be confirmed by X-ray powder diffraction (XRD) measurements or neutron scattering measurements.
[0080] Regarding the components constituting the solid electrolyte according to the present embodiment, the total content of elements constituting two or more types of agirodite-type crystal structures is preferably 80 mass% or more, more preferably 85 mass% or more, even more preferably 90 mass% or more, even more preferably 92 mass% or more, and particularly preferably 94 mass% or more from the perspective of realizing high lithium ion conductivity. Furthermore, the upper limit of the total content is not particularly limited and may be 100 mass%. In addition, the solid electrolyte according to the present embodiment may include crystals other than agirodite-type crystals or amorphous materials.
[0081] The sum of the above contents is, for example, the sum of Li, P, S, and Ha, and if oxide anions are included in the crystal, it is the sum of the contents of the elements Li, P, S, Ha, M, and O. In addition, in this specification, the content of Ha is the sum of the contents of F, Cl, Br, and I.
[0082] The content of each element or their total is determined by compositional analysis using ICP emission analysis, atomic absorption spectroscopy, ion chromatography, etc.
[0083] Other substances that may be included in the solid electrolyte include Li3PS4, Li4P2S6, Li2S, LiHa (where Ha is at least one halogen element selected from F, Cl, Br and I).
[0084] As an indicator of heat resistance, the thermal decomposition test temperature of the solid electrolyte is preferably 400°C or higher, more preferably 450°C or higher, even more preferably 500°C or higher, even more preferably 600°C or higher, and particularly preferably 650°C or higher. In addition, the upper limit is not specifically limited, but is typically 900°C or lower. However, in the case of an agirodite-type crystal with a high proportion of halogen elements, the thermal decomposition temperature tends to decrease. Therefore, considering the balance with the desired characteristics of the solid electrolyte, the composition of the agirodite-type crystal included in the solid electrolyte according to the present embodiment is selected.
[0085] In a heat decomposition test of a solid electrolyte, the heat resistance can be evaluated by placing the solid electrolyte in a sealed container that does not react with the solid electrolyte, performing heat treatment at a predetermined temperature for 10 to 60 minutes, and investigating the change in lithium ion conductivity before and after the heat treatment. It is desirable for the change in lithium ion conductivity before and after the heat treatment to be smaller, and if the lithium ion conductivity after heat treatment becomes less than half of the lithium ion conductivity before heat treatment, it can be said that the heat decomposition resistance, that is, the heat resistance, is low.
[0086] In addition, in this specification, lithium ion conductivity refers to the lithium ion conductivity at 25°C and is obtained from a Nyquist plot obtained by measuring AC impedance.
[0087] Method for manufacturing sulfide-based solid electrolytes
[0088] The method for manufacturing a sulfide-based solid electrolyte according to the present embodiment is Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2)로 표시되고, 수백㎚ 또는 수십㎚ 오더에서 병존하는 다른 2종 이상의 아기로다이트형의 결정 구조가 얻어지면 특별히 한정되지는 않는다.
[0089] As one embodiment, a manufacturing method comprising a process of mixing raw materials including Li, P, S and Ha and heating and melting them, followed by a process of crystallizing by rapid cooling is preferred. By rapid cooling under atmospheric pressure, a solid electrolyte is obtained in which two or more types of agirodite-type crystals coexist on the order of hundreds of nanometers or tens of nanometers.
[0090] The raw material containing Li, P, S, and Ha can be a material known in the past to obtain an agirodite-type crystal containing Li, P, S, and Ha.
[0091] Specifically, a suitable combination of Li element or a compound containing Li, P element or a compound containing P, S element or a compound containing S, and a compound containing Ha may be used. Such compounds may be compounds containing two or more of Li, P, S, and Ha. For example, phosphorus pentasulfide (P2S5) may be cited as a compound that combines a compound containing S and a compound containing P. In addition, lithium halide may be cited as a compound that combines a compound containing Li and a compound containing Ha.
[0092] Examples of compounds containing Li include lithium compounds such as lithium sulfide (Li2S), lithium carbonate (Li2CO3), lithium sulfate (Li2SO4), lithium oxide (Li2O), and lithium hydroxide (LiOH). From the perspective of ease of handling, it is preferable to use lithium sulfide.
[0093] Meanwhile, since lithium sulfide is expensive, from the perspective of suppressing manufacturing costs, it is desirable to use lithium compounds other than lithium sulfide or metallic lithium. Specifically, it is desirable to use one or more selected from the group consisting of metallic lithium, lithium carbonate (Li2CO3), lithium sulfate (Li2SO4), lithium oxide (Li2O), and lithium hydroxide (LiOH). These may be used individually or in combination of two or more types.
[0094] Examples of compounds containing S include phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5), other sulfur compounds containing phosphorus, elemental sulfur, and compounds containing sulfur. Examples of compounds containing sulfur include H2S, CS2, and iron sulfide (FeS, Fe2S3, FeS2, Fe 1-x (S, etc.), bismuth sulfide (Bi2S3), copper sulfide (CuS, Cu2S, Cu 1-x Examples include S, etc. Among these, phosphorus sulfide is preferred from the perspective of preventing the inclusion of elements other than those constituting the target sulfide-based solid electrolyte, and phosphorus pentasulfide (P2S5) is more preferred. These may be used alone or in combination of two or more types. In addition, phosphorus sulfide is a compound that is both a compound containing S and a compound containing P.
[0095] Examples of compounds containing P include phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5), and phosphorus compounds such as sodium phosphate (Na3PO4). Among these, phosphorus sulfide is preferred, and phosphorus pentasulfide (P2S5) is more preferred, from the perspective of preventing the inclusion of elements other than those constituting the target sulfide-based solid electrolyte. These may be used individually or in combination of two or more types.
[0096] Examples of compounds containing Ha include lithium halides such as lithium fluoride (LiF), lithium chloride (LiCl), lithium bromide (LiBr), and lithium iodide (LiI), phosphorus halides, phosphoryl halides, sulfur halides, sodium halides, and boron halides. Among these, lithium halides are preferred, and LiCl, LiBr, and LiI are more preferred, from the perspective of preventing the inclusion of elements other than those constituting the target sulfide-based solid electrolyte. These compounds may be used alone or in combination of two or more types.
[0097] The mixing of raw materials can be carried out, for example, by mixing in a mortar and pestle, mixing using media such as a planetary ball mill, or media-free mixing such as a fin mill, powder stirrer, or airflow mixing. The raw materials may be amorphized by mixing prior to heating.
[0098] The specific method of heating and melting the mixture of raw materials is not particularly limited, but for example, a method of placing the raw materials in a heat-resistant container and heating them in a furnace may be used. As for the heat-resistant container, examples include a heat-resistant container made of carbon, a heat-resistant container containing oxides such as quartz, quartz glass, borosilicate glass, aluminosilicate glass, alumina, zirconia, and mullite, a heat-resistant container containing nitrides such as silicon nitride and boron nitride, and a heat-resistant container containing carbides such as silicon carbide. In addition, such a heat-resistant container may be formed as a bulk of the above-mentioned materials, or it may be a container in which layers such as carbon, oxides, nitrides, and carbides are formed.
[0099] When heating and melting a mixture of raw materials, the heating temperature is preferably 600°C or higher, more preferably 630°C or higher, and even more preferably 650°C or higher from the perspective of increasing the fluidity of the molten liquid. In addition, from the perspective of suppressing deterioration or decomposition of components in the molten liquid due to heating, the heating temperature is preferably 900°C or lower, more preferably 850°C or lower, and even more preferably 800°C or lower.
[0100] From the perspective of carrying out the reaction, the heating and melting time is preferably 0.1 hours or more, more preferably 0.5 hours or more, more preferably 0.7 hours or more, and more preferably 1 hour or more. In addition, from the perspective of suppressing deterioration or decomposition of components in the molten liquid due to heating, the heating and melting time is preferably 10 hours or less, more preferably 9.5 hours or less, and more preferably 9 hours or less.
[0101] In addition, the pressure during heating and melting is not particularly limited, but specifically, atmospheric pressure or low pressure is preferred, and atmospheric pressure is more preferred.
[0102] In order to prevent adverse reactions with steam or oxygen during heating and melting, the dew point is preferably -20°C or lower, and while the lower limit is not particularly restricted, it is typically around -80°C. In addition, the oxygen concentration during heating and melting is preferably 1000 ppm or lower.
[0103] Crystallization is performed by rapidly cooling a mixture of heated and melted raw materials under atmospheric pressure. By doing so, a solid electrolyte is obtained in which two or more types of agirodite-type crystals, on the order of hundreds of nanometers or tens of nanometers, coexist.
[0104] Rapid cooling means that the cooling rate should be 1°C / second or higher, 10°C / second or higher is preferable, and 100°C / second or higher is more preferable. In addition, the upper limit of the cooling rate is not specifically limited, but if the cooling rate of a twin roller, which is generally considered to have the fastest rapid cooling rate, is added, the upper limit becomes 1,000,000°C / second or lower.
[0105] The lowering of atmospheric pressure during rapid cooling means that the pressure is not controlled during cooling. Specifically, it is about 0.8 to 1.2 atm.
[0106] Stabilization treatment may be performed by rapidly cooling under atmospheric pressure and then performing heat treatment again. Crystallinity is increased by heat treatment. Furthermore, depending on the heat treatment conditions, new agirodite-type crystals having a composition between the multiple agirodite-type crystals prior to heat treatment are also obtained.
[0107] The time for the heat treatment, which is a stabilization treatment, is preferably 0.1 hours or more and more than 0.2 hours from the perspective of more reliably performing crystal precipitation. In addition, from the perspective of obtaining new agirodite-type crystals, the heat treatment time is preferably 0.5 hours or more and more than 1 hour.
[0108] Meanwhile, from the perspective of suppressing thermal degradation by heating, the heat treatment time is preferably 10 hours or less, and more preferably 5 hours or less. In addition, from the perspective of preventing excessive crystallization from causing the lithium ion conductivity to drop too much, the heat treatment time is preferably 3 hours or less, and more preferably 2 hours or less.
[0109] The temperature of the heat treatment, which is a stabilization treatment, is preferably above the glass transition temperature of the solid electrolyte, specifically 200°C or higher, and more preferably 250°C or higher. In addition, from the perspective of obtaining new agirodite-type crystals, the heat treatment temperature is preferably 350°C or higher, and more preferably 400°C or higher.
[0110] Meanwhile, from the perspective of preventing thermal degradation or thermal decomposition, the heat treatment temperature is preferably below the thermal decomposition temperature, for example, 600°C or lower, and more preferably 575°C or lower. In addition, from the perspective of preventing excessive crystallization from causing the lithium ion conductivity to decrease too much, the heat treatment temperature is preferably 550°C or lower, and more preferably 530°C or lower.
[0111] When the solid electrolyte according to the present embodiment contains an oxide anion having a Q0 structure with an MO bond, the timing of adding the oxide having an MO bond is not particularly limited. For example, the oxide may be mixed with the raw material and heated to melt. In addition, the oxide may be mixed with a crystal obtained by rapid cooling under atmospheric pressure and subjected to heat treatment.
[0112] The obtained solid electrolyte, when used in a lithium-ion secondary battery, includes other components such as a binder as needed to form a solid electrolyte layer. The binder or other components are conventionally known.
[0113] The content of the solid electrolyte according to the present embodiment for the entire solid electrolyte layer is preferably 80 mass% or more, and more preferably 90 mass% or more. The upper limit of the solid electrolyte content is not particularly limited and may be 100 mass%. In addition, from the viewpoint of inhibiting deformation, inorganic fillers and organic fillers may be mixed, and in that case, the content of the solid electrolyte is preferably 99 mass% or less.
[0114] A conventionally known method is also used for forming a solid electrolyte layer. For example, a solid electrolyte layer can be formed by dispersing or dissolving a component constituting the solid electrolyte layer in a solvent to form a slurry, coating it into a layer shape (sheet shape), drying it, and pressing it as desired. If necessary, a debinding treatment may be performed by applying heat. The thickness of the solid electrolyte layer can be easily adjusted by adjusting the coating amount of the slurry.
[0115] In addition, instead of wet molding, a solid electrolyte layer may be formed by dry press molding of the solid electrolyte powder, etc., according to the present embodiment on the surface of a positive electrode or a negative electrode. Alternatively, a solid electrolyte layer may be formed on another substrate and transferred onto the surface of a positive electrode or a negative electrode.
[0116] The solid electrolyte according to the present embodiment may be mixed with a positive electrode active material or a negative electrode active material and used as a positive electrode layer or a negative electrode layer. The positive electrode active material or negative electrode active material, current collector, binder, conductivity aid, etc. used in the positive electrode layer or negative electrode layer may be conventionally known.
[0117] A lithium-ion secondary battery using the solid electrolyte according to the present embodiment comprises the solid electrolyte layer, a positive electrode layer, and a negative electrode layer.
[0118] The material of the casing of the lithium-ion secondary battery may also be conventionally known. The shape of the lithium-ion secondary battery may also be conventionally known, but examples include coin type, sheet type (film type), foldable type, cylindrical type with a wound bottom, button type, etc., and can be appropriately selected according to the application.
[0119] Examples
[0120] The present invention will be specifically described below with reference to examples, but the invention is not limited to these.
[0121] Examples 1, 2, and 4 to 9 are examples, and Example 3 is a comparative example.
[0122] [evaluation]
[0123] (Lithium ion conductivity)
[0124] The lithium ion conductivity was measured by using a powder of the obtained sulfide-based solid electrolyte as a measurement sample in a compact at a pressure of 380 kN and an AC impedance measuring device (Potentistat / Galvanostat VSP manufactured by Bio-Logic Sciences Instruments).
[0125] The measurement conditions were set as follows: measurement frequency: 100 Hz to 1 MHz, measurement voltage: 100 mV, measurement temperature: 25℃.
[0126] (Powder X-ray diffraction)
[0127] The XRD spectra of the sulfide-based solid electrolyte were measured using an X-ray diffraction device (SmartLab, manufactured by Rigaku). Since the sulfide-based solid electrolyte used as the measurement sample deteriorates when exposed to the atmosphere, the sample was prepared under an atmosphere free from atmospheric exposure and used for measurement.
[0128] Sample preparation: Sulfide-based solid electrolyte powder ground in a mortar and pestle is passed through a sieve with a mesh size of 100 µm to obtain a 50% particle size D 50A sulfide-based solid electrolyte powder with a particle size distribution of 5–10 µm was prepared. In addition, the particle size distribution was measured using a Microtrac MT3300EXII laser diffraction particle size analyzer, and from the obtained volume-based particle size distribution chart, the above 50% particle size D 50 Measured.
[0129] The measurement conditions for powder X-ray diffraction are as follows.
[0130] Source: CuKα line (λ=1.5418Å), Tube voltage: 45 kV, Tube current: 200 mA, Scan angle: 10–100°, Scan speed: 5° / min, Step count: 0.01° / step.
[0131] The analysis method for performing peak separation from the original data of the obtained XRD spectrum and the method for calculating the full width at half maximum are as follows.
[0132] Baseline removal and Cu-Kα2 line removal were performed using PDXL2, an integrated powder X-ray analysis software attached to an X-ray diffraction device (manufactured by Rigaku, SmartLab).
[0133] Next, focusing on the peak appearing at 2θ=30.3±0.5°, a pseudo-Voigt function for peak fitting was defined as Equation (1).
[0134]
[0135] In Equation (1), A represents the peak coefficient, B represents the height correction coefficient, ω represents the full width at half, and a represents the blending ratio. Equation (2) represents a Laurent-type function, and Equation (3) represents a Gaussian-type function. x0 is the peak center value and is expressed as the value of 2θ. Generally, when the XRD spectrum is expressed as the value of 2θ on the horizontal axis, it becomes a left-right asymmetric spectrum, so the blending ratio in Equation (1) is changed around the peak value (=x0) for interpretation.
[0136] The cause of this asymmetry is primarily attributed to the origin of the device and the penetration depth of the X-rays into the sample. Therefore, in this analysis, the hybridization ratio obtained from the analysis of Example 3, fabricated using the conventional solid-state method, was adopted. Specifically, 1.00 was used for the case where x0≥x, and x0 <x의 경우는 0.36을, 각각 채용했다. 이 혼성비를 사용하여, 실리콘 단일 결정의 피크를 해석한바 일치했다.
[0137] The Rwp metric was used to evaluate the consistency of the interpretation of the fitting function. This is a metric used in the Rietveld interpretation of XRD spectra.
[0138] For peaks appearing within the range of 2θ = 30.3 ± 0.5°, it is preferable that the value of Rwp obtained by applying one or more fitting functions defined above be as low as possible. Specifically, it is preferable that the value of Rwp be 15% or less, more preferable that it be 12.5% or less, and even more preferable that it be 10% or less. In addition, the value of Rwp is a positive value.
[0139] [Example 1]
[0140] Under a dry nitrogen atmosphere, lithium sulfide powder (Sigma, purity 99.98%), phosphorus pentasulfide powder (Sigma, purity 99%), and lithium chloride powder (Sigma, purity 99.99%) were weighed and mixed in a mortar and pestle to achieve a composition ratio of Li6PS5Cl. The resulting mixture was placed in a heat-resistant container and heated to melt at 730°C for 0.5 hours under an atmosphere with a dew point of -60°C. Subsequently, it was cooled to room temperature at a cooling rate of 10°C / second to obtain a solid that serves as a sulfide-based solid electrolyte.
[0141] Figure 1 shows the XRD spectrum of the obtained solid electrolyte near 2θ=30.3°. When peak separation was performed on the untreated spectrum shown as a solid line, three peaks were observed within the range of 2θ=30.3±0.5°. Details of these peaks are shown in Table 1.
[0142] As a result of the Rietveld analysis of the XRD spectrum, the diffraction peak at 2θ=29.99° corresponding to peak A of the obtained solid electrolyte is Li 6.9 PS 5.9 Cl 0.1 The diffraction peak at 2θ=30.11° corresponding to peak C, which is a peak originating from an agirodite-type crystal of the composition, is Li 5.9 PS 4.9 Cl 1.1 The diffraction peak at 2θ=30.24° corresponding to peak B, which is a peak originating from an agirodite-type crystal of the composition, is Li 5.5 PS 4.5 Cl 1.5 It was required that the peak be of origin from an agirodite-type crystal of the composition. The molar ratios of these three types of agirodite-type crystals are approximately, Li 6.9 PS 5.9 Cl 0.1 :Li 5.9 PS 4.9 Cl 1.1 :Li 5.5 PS 4.5 Cl 1.5 =2:1:3, and the lattice constants of these three types of agirodite crystals were 9.904 Å, 9.851 Å, and 9.804 Å, respectively.
[0143] "Basic composition" in Table 1 refers to the target composition when mixing the raw materials; in the case of Example 1, it is Li6PS5Cl, but the composition of the actually obtained agirodite-type crystal is Li, as determined from the above peaks A, B, and C. 6.9 PS 5.9 Cl 0.1 , Li 5.5 PS 4.5 Cl 1.5 and Li 5.9 PS 4.9 Cl 1.1 This coexisted and is different from the basic composition.
[0144] In Table 1, the “-” for Peak A or Peak B indicates that the peak was lost or that the peak intensity ratio was so small that the peak could not be detected. Additionally, the peak intensity ratio is the relative intensity ratio expressed by setting the sum of the peak intensities of Peak A, Peak B, and Peak C to 1.
[0145] [Example 2]
[0146] A sulfide-based solid electrolyte was obtained by performing heat treatment on the solid obtained in Example 1 at 500°C for 1 hour under a nitrogen atmosphere. The XRD spectrum of the obtained solid electrolyte near 2θ=30.3° is shown in Figure 2. When peak separation was performed on the untreated spectrum shown as a solid line, two peaks were observed within the range of 2θ=30.3±0.5°. Details of the peaks are shown in Table 1.
[0147] As a result of the Rietveld analysis of the XRD spectrum, the obtained solid electrolyte is Li 5.9 PS 4.9 Cl 1.1 :Li 5.5 PS 4.5 Cl 1.5 It was found that it has two types of agirodite crystals with a molar ratio of 5:1.
[0148] [Example 3]
[0149] The same mixture as in Example 1 was mixed using a planetary ball mill at 400 rpm for 4 hours. The resulting mixture was vacuum-sealed in a carbon-coated quartz tube and heated at 550°C for 5 hours to obtain a solid that becomes a sulfide-based solid electrolyte. In the XRD spectrum of the obtained solid electrolyte, one peak was observed within the range of 2θ = 30.3 ± 0.5°. Details of the peak are shown in Table 1.
[0150] As a result of Rietveld analysis of the XRD spectrum, it was found that the obtained solid electrolyte had a type of agarodite crystal of Li6PS5Cl.
[0151] [Example 4]
[0152] Li 5.4 PS 4.4 Cl 1.6 A solid constituting a sulfide-based solid electrolyte was obtained by following the same procedure as in Example 1, except that a mixture of weighed lithium sulfide powder (Sigma, purity 99.98%), phosphorus pentasulfide powder (Sigma, purity 99%), and lithium chloride powder (Sigma, purity 99.99%) was prepared to achieve the compositional ratio. In the XRD spectrum of the obtained solid electrolyte, three peaks were identified within the range of 2θ = 30.3 ± 0.5°, corresponding to 2θ = 30.15°, 30.29°, and 30.33°, respectively. Among these, the two peaks at 2θ = 30.29° and 2θ = 30.33°, which have a difference in diffraction angle of less than 0.05°, have nearly similar compositions and Li 5.4 PS 4.4 Cl 1.6 It is presumed to possess two types of agirodite-type crystals with a composition close to that of Li. The agirodite-type crystal having a peak at 2θ=30.15° is Li 5.7 PS 4.7 Cl 1.7 It is presumed to be close to the composition of.
[0153] [Example 5]
[0154] A sulfide-based solid electrolyte was obtained by further heat-treating the solid obtained in Example 4 at 450°C for 1 hour under a nitrogen atmosphere. In the XRD spectrum of the obtained solid electrolyte, three peaks were observed within the range of 2θ = 30.3 ± 0.5°. Compared to the peak of Example 4, the peak intensity ratio on the high-angle side corresponding to peak B was higher. From the results of compositional analysis, no change in composition was observed before and after heat treatment. Therefore, the obtained solid electrolyte is Li 5.4 PS 4.4 Cl 1.6 It is composed of, and can also be said to have an agirodite-type crystal with a lower lattice constant than before heat treatment.
[0155] [Example 6]
[0156] Li 5.6 PS 4.4 Cl 1.5 Br 0.2 A solid constituting a sulfide-based solid electrolyte was obtained by following the same procedure as in Example 1, except that a mixture was prepared by weighing lithium sulfide powder (Sigma, purity 99.98%), phosphorus pentasulfide powder (Sigma, purity 99%), lithium chloride powder (Sigma, purity 99.99%), and lithium bromide powder (Sigma, purity 99.995%) to achieve the compositional ratio. In the XRD spectrum of the obtained solid electrolyte, three peaks were identified within the range 2θ = 30.3 ± 0.5°, corresponding to 2θ = 30.16°, 30.34°, and 30.41°, respectively. Among these, the peak corresponding to peak C at 2θ = 30.34° corresponds to Li 5.6 PS 4.4 Cl 1.5 Br 0.2 It is presumed to be of the origin of an agirodite-type crystal with a composition close to that of peak A and peak B, and the two peaks corresponding to peak A and peak B are presumed to be of an agirodite-type crystal with a composition or lattice constant slightly different from that of peak A and peak B.
[0157] [Example 7]
[0158] A sulfide-based solid electrolyte was obtained by further heat-treating the solid obtained in Example 6 at 450°C for 1 hour under a nitrogen atmosphere. In the XRD spectrum of the obtained solid electrolyte, two peaks were observed within the range of 2θ = 30.3 ± 0.5°. Compared to the peak of Example 6, the peak intensity ratio on the high-angle side corresponding to peak B was higher. From the results of compositional analysis, no change in composition was observed before and after heat treatment. Therefore, the obtained solid electrolyte is Li 5.6 PS 4.4 Cl 1.5 Br 0.2It is composed of, and can also be said to have an agirodite-type crystal with a lower lattice constant than before heat treatment.
[0159] [Example 8]
[0160] Li 5.6 PS 4.4 Cl 0.8 Br 0.8 A solid constituting a sulfide-based solid electrolyte was obtained by following the same procedure as in Example 1, except that a mixture was prepared by weighing lithium sulfide powder (Sigma, purity 99.98%), phosphorus pentasulfide powder (Sigma, purity 99%), lithium chloride powder (Sigma, purity 99.99%), and lithium bromide powder (Sigma, purity 99.995%) to achieve the compositional ratio. In the XRD spectrum of the obtained solid electrolyte, three peaks were identified within the range 2θ = 30.3 ± 0.5°, corresponding to 2θ = 30.05°, 30.14°, and 30.33°, respectively. Among these, the peak at 2θ = 30.14°, corresponding to peak C, was Li 5.6 PS 4.4 Cl 0.8 Br 0.8 It is presumed to be of the origin of an agirodite-type crystal with a composition close to that of peak A and peak B, and the two peaks corresponding to peak A and peak B are presumed to have an agirodite crystal with a composition or lattice constant slightly different from that.
[0161] [Example 9]
[0162] A sulfide-based solid electrolyte was obtained by further heat-treating the solid obtained in Example 8 at 450°C for 1 hour under a nitrogen atmosphere. In the XRD spectrum of the obtained solid electrolyte, two peaks were observed within the range of 2θ = 30.3 ± 0.5°. The peak at 2θ = 30.14°, corresponding to peak C which has a large peak intensity ratio and can be considered the main peak, became sharper and its intensity ratio increased through heat treatment. Consequently, Li, which has increased crystallinity 5.6 PS 4.4 Cl 0.8 Br0.8 It is presumed that it has an agirodite-type crystal composition.
[0163]
[0164] In Examples 1, 2, and 4 through 9, the hybrid ratio during fitting analysis, represented by parameter a of Equation (1), was the same value as in Example 3. All analysis results showed that Rwp was 15% or less, which was a good value.
[0165] From the above results, the sulfide-based solid electrolyte of Example 3, obtained by the conventional solid-state method, contained one type of agirodite-type crystal, and the lithium ion conductivity was 1.2 mS / cm. Meanwhile, the solid electrolytes of Examples 1 and 2 contained two or three types of agirodite-type crystals, despite having the same type and amount of raw materials as Example 3. The lithium ion conductivity was 3.1 mS / cm and 2.7 mS / cm, respectively, showing very high values compared to Example 3.
[0166] When comparing Examples 1 and 2, 4 and 5, 6 and 7, and 8 and 9, it was found that performing heat treatment sharpened the peaks of the XRD spectra, and the lattice constant tended to concentrate in the crystal exhibiting the central peak or decrease. Consequently, it is believed that the Coulomb interactions within the crystal are enhanced, thereby improving heat resistance, chemical stability, and electrochemical stability. Furthermore, although the lithium-ion conductivity decreased slightly after heat treatment compared to before, it still showed a high value when compared to the solid electrolyte of Example 3, which contained only one type of agirodite-type crystal.
[0167] Although the reason why the lithium ion conductivity is increased by including two or more types of arhodite-type crystals is not clear, it is realized in the case of arhodite-type crystals obtained by undergoing a melting process and rapidly cooling therefrom in the manufacture of a solid electrolyte. Therefore, it is thought that the seed crystal initially precipitated during the cooling process from the molten state is a high-temperature stable phase, and the arhodite-type crystals grown using that seed crystal as a nucleus have lithium ion, sulfur anion, and halogen anion sites that are different from those produced by a normal solid-state reaction. Generally, high-temperature stable phases tend to have high ion conductivity, and it is thought that high lithium ion conductivity can be realized in the arhodite-type crystals according to the present embodiment because arhodite-type crystals of multiple compositions containing the high-temperature stable phase are precipitated during cooling from the molten state.
[0168] Although the present invention has been described in detail with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the invention. This application is based on Japanese patent application filed on October 13, 2020 (Patent Application No. 2020-172693), the contents of which are incorporated herein by reference.
Claims
Claim 1 It is a sulfide-based solid electrolyte used in lithium-ion secondary batteries, and Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2이고, Ha은 할로겐 원소이다.)로 표시되는 아기로다이트형의 결정 구조를 갖고,Cu-Kα선을 사용한 X선 회절 스펙트럼에 있어서, 상기 아기로다이트형의 결정 구조는, 2θ=30.3±0.5°의 범위 내에 반값 전폭이 각각 0.07° 이상인 피크 A 및 피크 B를 갖고,상기 피크 A 및 상기 피크 B의 회절각(2θ)의 차는 0.05° 이상인, 황화물계 고체 전해질. Claim 2 A sulfide-based solid electrolyte according to claim 1, wherein peak A and peak B are peaks originating from two types of agirodite-type crystal structures with lattice constants different by 0.02 Å or more. Claim 3 A sulfide-based solid electrolyte according to claim 1 or 2, wherein at least one phenomenon selected from (i) to (iii) below is observed in an X-ray diffraction spectrum using Cu-Kα rays after heat treatment for 1 hour at a temperature of 400°C or higher and a pyrolysis temperature or lower: (i) a decrease in the peak intensity ratio of peak A; (ii) an increase in the peak intensity ratio of peak B; (iii) the appearance of peak C which is on the higher angle side than peak A and on the lower angle side than peak B, or an increase in the peak intensity ratio of peak C. Claim 4 In paragraph 3, a sulfide-based solid electrolyte having peak C between peak A and peak B. Claim 5 It is a sulfide-based solid electrolyte used in lithium-ion secondary batteries, and Li a PS b Ha c (5≤a≤7, 4≤b≤6 also 0 <c≤2이고, Ha은 할로겐 원소이다.)로 표시되는 아기로다이트형의 결정 구조를 갖고,Cu-Kα선을 사용한 X선 회절 스펙트럼에 있어서, 상기 아기로다이트형의 결정 구조는, 2θ=30.3±0.5°의 범위 내에 반값 전폭이 각각 0.07° 이상인, 피크 D 및 피크 E를 갖고,상기 피크 D 및 상기 피크 E의 회절각(2θ)의 차는 0.02∼0.4°이고,400℃ 이상 열분해 온도 이하의 온도에서 1시간의 열처리를 행해도, 상기 X선 회절 스펙트럼이 변화되지 않는, 황화물계 고체 전해질. Claim 6 delete Claim 7 delete
Citation Information
Patent Citations
High-performance all-solid lithium battery
KR1020070017190A
Solid electrolyte
KR1020140096273A
Sulfide-based solid electrolyte for lithium secondary batteries
KR1020190007028A
An all solid secondary battery
KR1020200057585A
Crystalline solid electrolyte
JP2018049834A
